Survey Says ... : Corporate Governance Matters to Investors in Emerging Market Companies - Khanna, Vikramaditya (International Finance Corporation, Washington, D.C., 2017)
Financial crises have a way of bringing corporate governance to the foreground. For interested parties wanting to know more, there is an impressive body of research that looks at companies and the connection between strong governance and better performance. However, the existing literature only goes so far. It does not look at whether the level and quality of firm-level corporate governance plays a role as large-scale investors consider investment decisions in emerging markets. This study of emerging market investors sheds light on this issue and reveals that emerging market investors care deeply about corporate governance. The findings have significant implications, not only for the emerging markets business and finance community, but for policy makers, academics, the media, as well as for development finance institutions focused on sustainable economic development in these countries. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.